Breakpoints around the HOXD cluster result in various limb malformations. Issue 2 (24th June 2005) - Dlugaszewska, B; Silahtaroglu, A; Menzel, C; Kübart, S; Cohen, M; Mundlos, S; Tümer, Z; Kjaer, K; Friedrich, U; Ropers, H-H; Tommerup, N; Neitzel, H; et al.
Abstract : Background: Characterisation of disease associated balanced chromosome rearrangements is a promising starting point in the search for candidate genes and regulatory elements. Methods: We have identified and investigated three patients with limb abnormalities and breakpoints involving chromosome 2q31. Patient 1 with severe brachydactyly and syndactyly, mental retardation, hypoplasia of the cerebellum, scoliosis, and ectopic anus, carries a balanced t(2;10)(q31.1;q26.3) translocation. Patient 2, with translocation t(2;10)(q31.1;q23.33), has aplasia of the ulna, shortening of the radius, finger anomalies, and scoliosis. Patient 3 carries a pericentric inversion of chromosome 2, inv(2)(p15q31). Her phenotype is characterised by bilateral aplasia of the fibula and the radius, bilateral hypoplasia of the ulna, unossified carpal bones, and hypoplasia and dislocation of both tibiae. Results: By fluorescence in situ hybridisation, we have mapped the breakpoints to intervals of approximately 170 kb or less. None of the three 2q31 breakpoints, which all mapped close to the HOXD cluster, disrupted any known genes. Conclusions: Hoxd gene expression in the mouse is regulated by cis -acting DNA elements acting over distances of several hundred kilobases. Moreover, Hoxd genes play an established role in bone development. It is therefore very likely that the three rearrangements disturb normal HOXD gene regulation by position effects.